Coordination within Conversational Agents with Multiple Sources - Matos, Vinícius Bitencourt; Grava, Ricardo; Tavares, Rodrigo; José, Marcos Menon; Pirozelli, Paulo; Brandão, Anarosa A. F.; Peres, Sarajane M.; Cozman, Fábio G. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2023)
Conversational agents can now operate with language models, rules, ontologies and varied other sources to provide smooth dialogue. However, the coordination of multiple sources in conversational agents is a challenge. We present a mechanism to effectively orchestrate multiple sources in a conversational agent, by relying on a client-server approach with an associated prompt generation module that deals with heterogeneous domain-oriented modules. As a detailed use case, we describe the architecture of a chatbot specialised in topics related to the Brazilian coast, and we study the benefits of our approach.